Corporate Board Attributes and Dividend Payout Likelihood - Adamu, Idris Adamu; Ishak, Rokiah; Hassan, Nor Laili (Journal of Reviews on Global Economics, 2019)
Extant literature has shown that corporate governance influences dividends policy. However, the effect of diversity on the likelihood to distribute cash dividends is scarce in the literature. Therefore, this study is aimed at exploring the influence of gender diversity and financial expertise on the likelihood of dividends payout. Pooled logistic regression was used on a sample of data from non-financial listed firms in Nigeria spanning from 2009 to 2015. The study documents gender diversity and financial experts have significant effect on a firm’s likelihood to distribute cash dividends. The results remain unchanged after adjusting the standard errors for clustering at a firm. The overall finding suggests that diversity in terms of gender and expertise play a critical role all things being equal in determining the decision to pay cash dividends shareholders of listed firms in Nigeria.